Spontaneous rupture of the lymph nodes as a cause of haemoabdomen in two canine lymphoma patients - Tanja Plavec; Tanja Svara; Natasa Tozon; Darja Pavlin (Veterinární Medicína, 2020)
Non-traumatic haemoabdomen in dogs usually occurs due to abdominal neoplasia, coagulopathies or organ torsion. The most common sources of bleeding in neoplastic cases are the spleen and liver, but other abdominal organs can also be involved. However, in the available veterinary literature, ruptured lymph nodes are not described as a cause of haemoabdomen. In the present manuscript, two canine cases of intra-abdominal haemorrhage from ruptured lymph nodes secondary to B-cell lymphoma are described.